2016
DOI: 10.1115/1.4033092
|View full text |Cite
|
Sign up to set email alerts
|

Using Nonlinear Kinematic Hardening Material Models for Elastic–Plastic Ratcheting Analysis

Abstract: Applicable design codes for power plant components and pressure vessels demand for a design check against progressive plastic deformation. In the simplest case, this demand is satisfied by compliance with shakedown rules in connection with elastic analyses. The possible noncompliance implicates the requirement of ratcheting analyses on elastic–plastic basis. In this case, criteria are specified on maximum allowable accumulated growth strain without clear guidance on what material models for cyclic plasticity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The detailed calibration procedures for determining a set of Chaboche kinematic hardening parameters (C 1 –γ 1 , C 2 –γ 2 and C 3 –γ 3 ) were suggested in the literature. 48 Table 3 shows the Chaboche material parameters for different heat-treated samples containing 30%, 35% and 68% martensite, respectively, and thereby observed that the prediction of a cyclic stress–strain curve with those Chaboche parameters exactly matches with the cyclic deformation behaviour of constituent phases as shown in Figure 10.…”
Section: Micromechanical Fe Modellingmentioning
confidence: 59%
“…The detailed calibration procedures for determining a set of Chaboche kinematic hardening parameters (C 1 –γ 1 , C 2 –γ 2 and C 3 –γ 3 ) were suggested in the literature. 48 Table 3 shows the Chaboche material parameters for different heat-treated samples containing 30%, 35% and 68% martensite, respectively, and thereby observed that the prediction of a cyclic stress–strain curve with those Chaboche parameters exactly matches with the cyclic deformation behaviour of constituent phases as shown in Figure 10.…”
Section: Micromechanical Fe Modellingmentioning
confidence: 59%
“…Rudolph et al [6] used ABAQUS finite element analysis software to analyze the constitutive model of metallic materials.In this paper, the unidirectional tensile test and tensile-compression test of the round bar intercepted in X80 sheet are carried out, and the basic mechanical parameters of the material are obtained.The ABAQUS finite element analysis software was used to establish the same simulation scheme as the experiment. The kinematic hardening model of ABAQUS material library and the kinematic hardening model defined by UMAT are used to calculate and compare the stress-strain curves and the experimental curves respectively.The results show that the effect of the kinematic hardening model defined by the UMAT subroutine is in accordance with the experimental results.…”
Section: Establishment Of the Kinetic Hardening Model Of Pipeline Steelmentioning
confidence: 99%